2015
DOI: 10.1371/journal.pone.0116712
|View full text |Cite
|
Sign up to set email alerts
|

Proliferation and Differentiation of Trypanosoma cruzi inside Its Vector Have a New Trigger: Redox Status

Abstract: Trypanosoma cruzi proliferate and differentiate inside different compartments of triatomines gut that is the first environment encountered by T. cruzi. Due to its complex life cycle, the parasite is constantly exposed to reactive oxygen species (ROS). We tested the influence of the pro-oxidant molecules H2O2 and the superoxide generator, Paraquat, as well as, metabolism products of the vector, with distinct redox status, in the proliferation and metacyclogenesis. These molecules are heme, hemozoin and urate. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
75
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 80 publications
(81 citation statements)
references
References 50 publications
(61 reference statements)
6
75
0
Order By: Relevance
“…The in vitro growth of T. cruzi epimastigotes in LIT cutlure medium has been extensively described in the literature [15][16][17]. Our findings are in accordance with such descriptions.…”
Section: Discussionsupporting
confidence: 92%
“…The in vitro growth of T. cruzi epimastigotes in LIT cutlure medium has been extensively described in the literature [15][16][17]. Our findings are in accordance with such descriptions.…”
Section: Discussionsupporting
confidence: 92%
“…In addition to the described metabolic uniqueness, our results showed that these processes are differentially used in both phases of epimastigote growth. Interestingly, recently it was suggested that epimastigote proliferation requires an oxidative environment to happen, whereas differentiation occurs in a more reductive setting (34).…”
Section: Discussionmentioning
confidence: 99%
“…Several factors have been described as involved in triggering this differentiation, such as availability of nutrients, intracellular cAMP levels and amino acid metabolism (reviewed by Goldenberg and Rodrigues Ávila, [16]) and, more recently, redox status [17]. Although it is known that metacyclogenesis can be induced in vitro by incubating epimastigotes in TAU3AAG, a chemically defined medium that mimics the urine of triatomine bugs [18], the exact events that induce this process are unknown so far.…”
Section: Discussionmentioning
confidence: 99%